Dietary glycemic index, glycemic load, and lung cancer risk: A case-control study in Los Angeles County. (December 2020) - Chang, Chun-Pin; Meyers, Travis J.; Fu, Alan; Zhang, Ming-Yan; Tashkin, Donald P.; Rao, Jian-Yu; Cozen, Wendy; Mack, Thomas M.; Hashibe, Mia; Morgenstern, Hal; Zhang, Zuo-Feng
Highlights: Glycemic index was associated with increased lung cancer risk. Positive associations of glycemic index on adenocarcinoma and small cell carcinoma. Stronger associations in individuals who had smoked, BMI < 25, and no diabetes history. Abstract: Background: Although there is some evidence of positive associations between both the glycemic index (GI) and glycemic load (GL) with cancer risk, the relationships with lung cancer risk remain largely unexplored. We evaluated the associations between GI and GL with lung cancer. Methods: The analyses were performed using data from a population-based case-control study recruited between 1999 and 2004 in Los Angeles County. Dietary factors were collected from 593 incident lung cancer cases and 1026 controls using a modified food frequency questionnaire. GI and GL were estimated using a food composition table. Adjusted odds ratios (ORs) and 95 % confidence intervals (CI) were estimated using unconditional logistic regression adjusting for potential confounders. Results: Dietary GI was positively associated with lung cancer (OR for upper vs. lower tertile = 1.62; 95 % CI: 1.17, 2.25). For histologic subtypes, positive associations were observed between GI and adenocarcinoma (OR for upper vs. lower tertile = 1.82; 95 % CI: 1.22, 2.70) and small cell carcinoma (OR for upper vs. lower tertile = 2.68; 95 % CI: 1.25, 5.74). No clear association between GL and lung cancer was observed. Conclusion: These findings suggest that high dietary GI was associated with increased lung cancer risk, and the positive associations were observed for both lung adenocarcinoma and small cell lung carcinoma. Replication in an independent dataset is merited for a broader interpretation of our results.